2012
DOI: 10.1111/j.1464-410x.2012.11337.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the impact of urinary tract infections on health‐related quality of life

Abstract: What ' s known on the subject? and What does the study add? Values for equivalent health states can vary substantially depending on the measure used and method of valuation; this has a direct impact on the results of economic analyses. To date, the majority of existing economic evaluations that include UTI as a health state refer to an analysis in which the Index of Well Being was used to estimate the quality of life experienced by young women with UTIs. Currently, there are no validated methods or fi lters fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 23 publications
3
38
1
5
Order By: Relevance
“…Although UTIs are usually mild, recurrent UTIs have detrimental effects on the quality of life of patients and on healthcare systems [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although UTIs are usually mild, recurrent UTIs have detrimental effects on the quality of life of patients and on healthcare systems [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infections (UTIs) are the most common nosocomial infection and can increase the length of intensive care unit stay, morbidity and costs [1,2,3]. In particular, Pseudomonas aeruginosa UTIs are associated with a high mortality and morbidity [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies30 31 and a review32 were found that reported utility values for SCI patients experiencing UTIs. The first one30 reported utility values (estimated by HUI-Mark III health status classification system) of 0.28 and 0.15 for no/mild UTI and moderate/significant UTI, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The second study31 reported utility values for UTI of 0.58 and 0.60 estimated by SF36 and SF12 questionnaires, respectively. The review32 included an additional study conducted by Vogel and Zebracki from which utility values of 0.831, 0.782 and 0.738 were estimated for no UTI, UTI and severe UTI, respectively. From the database search, no utility values were found for haematuria and bacteraemia health states.…”
Section: Methodsmentioning
confidence: 99%